1993
DOI: 10.1161/01.cir.87.6.1873
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of aspirin on carotid atherosclerosis.

Abstract: The results of our study indicate that aspirin treatment slows carotid plaque growth in a dose-dependent fashion, with a dose of 900 mg daily more efficient than 50 mg daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…14 Although the authors as well as previous studies already highlighted that blocking platelet CD40L might reduce thrombus formation and stability, 1,15 the current report identifies-for the first time-that blocking platelet CD40L might preserve the natural T reg response, as a potential novel mechanism to explain the putative plaquegrowth-suppressing effects of antiplatelet drugs.…”
mentioning
confidence: 62%
“…14 Although the authors as well as previous studies already highlighted that blocking platelet CD40L might reduce thrombus formation and stability, 1,15 the current report identifies-for the first time-that blocking platelet CD40L might preserve the natural T reg response, as a potential novel mechanism to explain the putative plaquegrowth-suppressing effects of antiplatelet drugs.…”
mentioning
confidence: 62%
“…First, the pharmacokinetics of aspirin in mice could be different from that in humans; second, whereas humans get a once-daily administration, the animals in our study had a multiple daily dosing. Considering the existence of relatively little literature on the effect of this drug on atherosclerosis, 27,28 our observations suggest that a reevaluation of aspirin in atherosclerotic plaque progression and composition in humans is timely.…”
Section: Discussionmentioning
confidence: 94%
“…32 Indeed, some clinical treatment studies already exist that show a causal role for platelet activity and progression of IMT of the carotid artery. Ranke et al 33 showed that aspirin treatment slowed carotid plaque growth in a dose-dependent manner, with a dose of 900 mg daily more efficient than 50 mg daily. Kodama et al 34 evaluated the effectiveness of long-term antiplatelet therapy in attenuating progression of IMT of the carotid artery of subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%